THE RELATIONSHIP BETWEEN ADVERSITY QUOTIENT WITH PSYCHOLOGICAL DISTRESS IN STUDENTS OF MEDICAL STUDY PROGRAMS IN SEBELAS MARET UNIVERSITY SURAKARTA - Galuh Maitri Imantaka Dharma; Istar Yuliadi; Rini Setyowati (Philanthropy: Journal of Psychology, 2020)
The Medical Study Program causes many new situational demands and has the potential to create stress on students. The high number of lecture material difficulties, the number of assignments, the demands to understand the lecture material in a relatively short time and other problems that arise in the personal lives of students can trigger stress on medical students. Medical students who have a relatively high level of adversity quotient have a better tendency to deal with and deal with stressors in order to minimize the occurrence of psychological distress.This study aims to determine the relationship between adversity quotient with psychological distress in medical students at Sebelas Maret University Surakarta. Respondents in this study amounted to 90 students consisting of classes 2017, 2018, and 2019 with an age range of 18-21 years and are still actively attending lecture activities. The sampling technique used in this study was proportionate stratified random sampling. The instrument used in this study was a psychological distress scale (Î± = 0.934) and an adversity quotient scale (Î± = 0.951). The correlation test in this study used the Pearson Product Moment correlation test.Based on the Pearson Product Moment correlation test results obtained rxy = -0,525; p = 0,000 (p <0.05). This shows that there is a significant negative relationship between adversity quotient with psychological distress in medical students of Sebelas Maret University Surakarta. The higher adversity quotient, the lower psychological distress in medical students of Sebelas Maret University Surakarta, and conversely.